Remote school gardens: exploring a cost‐effective and novel way to engage Australian Indigenous students in nutrition and health - Andrew Hume; Alexander Wetten; Camilla Feeney; Sally Taylor; Kerin O'Dea; Julie Brimblecombe (Elsevier, 2014)
Abstract Objective: This pilot study aimed to determine the feasibility of a novel, low‐cost program to get remote schools started in gardening and nutrition activities, for a lower cost than existing models, and without on‐the‐ground horticultural support. Methods: A multi‐site, mixed methods case study was undertaken, in which four remote schools were shipped gardening materials and a nutrition and cooking resource, and provided with horticultural support by phone and email. A support register and teacher surveys were used for four months of evaluation. Results: The study demonstrated that the program is feasible, and may be associated with an increase from baseline in student's time spent cooking, gardening and on related classroom activities. Conclusions: The program was delivered economically without the need for on‐the‐ground staff, in a manner that was acceptable to teachers. Implications: This model may have application in remote schools throughout Australia, where there is a need to alter health impacting behaviours in high‐risk populations. Lengthier program evaluation times and further resource development may be worth investigating in the future.